2007
DOI: 10.1002/lapl.200710056
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography imaging depth enhancement by superficial skin optical clearing

Abstract: Non-invasive imaging of human skin and human skin tissues by optical coherence tomography (OCT) is a field exciting a great deal of interest especially in terms of day-to-day medical and biomedical diagnostics. We develop rapid scanning OCT system for non-invasive real-time imaging of topical skin tissues in vivo. We investigate the possibility of OCT image enhancement along the transcutaneous diffusion into the skin an optical clearing agent. Diffusion of optical clearing agents, e.g. such as glycerol, tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…Finally, the LSCI can be applied to obtain better image quality for monitoring the cutaneous microcirculation. However, the similar improvement in blood vessels imaging using OCT could be not found at application of glycerol as an OCA [64][65][66]. The main reasons may be from the two aspects: firstly, thiazone, as a chemical penetration agent, was used in our work, could significantly enhance the skin optical clearing efficacy [39][40][41], as well as the penetration of glycerol into skin sample is relatively limited [29,67,68].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Finally, the LSCI can be applied to obtain better image quality for monitoring the cutaneous microcirculation. However, the similar improvement in blood vessels imaging using OCT could be not found at application of glycerol as an OCA [64][65][66]. The main reasons may be from the two aspects: firstly, thiazone, as a chemical penetration agent, was used in our work, could significantly enhance the skin optical clearing efficacy [39][40][41], as well as the penetration of glycerol into skin sample is relatively limited [29,67,68].…”
Section: Discussionmentioning
confidence: 81%
“…Thus, dynamic speckle signals can be detected easily through the transparent skin. Previous investigation indicated that increasing transparency of skin could significantly improves depth of imaging, image contrast and spatial resolution [64]. Finally, the LSCI can be applied to obtain better image quality for monitoring the cutaneous microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, various mechanisms are involved, such as the dissociation of collagen 15,16 , the ability to disrupt the hydration shell and the water-mediated hydrogen bonds of collagen molecules, 17 and the dehydration process 10,[18][19][20] . In addition to penetration depth enhancement for tissue imaging [21][22][23] , OCAs also enable optical blood clearing 24 and monitoring of molecular diffusion [25][26][27][28][29][30] using OCT systems. Whereas OCA approaches use the scattering properties of tissue samples for the enhancement of the penetration depth, it has been recently demonstrated that controlling the illumination light in optical imaging can offer a high possibility of overcoming multiple scattering without affecting the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is difficult to register the Doppler shift of the carrier itself when applying ultrafast scanning techniques, [3][4][5][6][7][8][9][10][11][12][13][14] f D ¼ AE2V cosðαÞ∕λ 0 , we use the modified double pass rapid scanning optical delay (RSOD) 18,19 at lower scanning frequencies. RSOD allows the decoupling phase and group delay, as well as a shift of f c to the values of 20 to 30 kHz.…”
Section: Introductionmentioning
confidence: 99%